Estudo sobre as concepções de professores do ensino básico em relação à aleatoriedade e probabilidade - Rodrigues, Marcelo Rivelino (2018)
Probabilistic knowledge is relevant to life in society, since well-founded decision-making can help provide a competitive edge both in the labor market and daily life. The present study investigated the conceptions of probability and randomness held by basic education teachers when faced with questions that address these topics. Data were collected from 41 sixth- do ninth-grade Brazilian teachers who responded to “Probabilistic Concepts Questionnaire”, applied to reveal the conceptions of probability held by the group. The multidimensional data were interpreted by subjecting the teachers’ responses to implicative and cohesive analysis, using Hierarchical, Implicative, and Cohesive Classification (CHIC) software, which yielded cohesion and implication graphs of the relationships operating among the variables investigated. The categorizations delineated by Azcárate and Cardeñoso for conceptions of probability, as well as the definition of probabilistic literacy formulated by Gal, provided the theoretical framework for the study. Two official educational guidelines—the Brazilian Curricular Guidelines (locally referred to as PCN) and the Brazilian Common Curricular Basis (BNCC)—were compared to detect similarities and pinpoint changes made to these documents with regard to the teaching of probability in basic education. In addition, Chevallard’s Anthropological Theory of the Didactic was employed to identify the types of tasks, techniques, and theories present in a mathematics textbook series approved by the National Textbook Program (PNLD). The analysis evidenced the probabilistic conceptions held by the participants, in the dimensions of randomness and probability. Four groups were identified in each dimension. Dimension randomness: deterministic; causality; multiplicity; uncertainty. Probability dimension: indefinite; causality; deterministic; uncertainty; subjectivity. The analysis evidenced the probabilistic conceptions held by the participants, in the dimensions of randomness and probability. In the randomness dimension, six groups of conceptions were identified: determinism; causality; multiplicity; uncertainty; standard; undefined. The probability dimension comprised five groups: causality; determinism; uncertainty; contingency; personalist. The investigation shed light on the conceptions of probability held by the participants, allowing probabilistic literacy levels to be categorized